(untitled) (Jurnal Kemanusiaan, 2018)
This study aims to examine the job satisfaction among employees in one of the Malaysian banking institutions. In particular the study explores the differences between intrinsic and extrinsic satisfaction factors. Multistage sampling was employed in this study, whereby simple random sampling and cluster sampling were used. A quantitative (survey) method was employed in this study, in which questionnaires were distributed to 353 bank employees (managerial and non-managerial), but with only 174 valid responses received. The data were then analysed using descriptive statistics and one sample t-test through the Statistical Package for the Social Sciences (SPSS) version 22.0. Based on the findings, the employees at the banking institution were slightly satisfied with their jobs. One sample t-test revealed that the intrinsic and extrinsic satisfaction factors are significantly positive. Hence, the results call upon the management of the bank institution to foster both intrinsic and extrinsic satisfaction factors in order to enhance the employeesâ€™ satisfaction that will link to the increase of the organisationâ€™s productivity.Â